Urban vegetation of the Anatolian side of Istanbul - YARCI, CELAL (GEBRUDER BORNTRAEGER, 2020)
Aims: We present the first survey of plant communities of Istanbul, their classification and syntaxonomy with main environmental drivers that shape them. Study area: Anatolian (Asian) part of Istanbul, Turkey. Methods: We collected 442 vegetation releves according to Braun-Blanquet method. Cluster analysis and ordination of the dataset were performed to assess particular vegetation patterns. Diagnostic species of each cluster were determined using the fidelity measure (phi-coefficient). Site conditions were presented by ecological indicator values. Results: The analysed dataset shows clear division into six classes. They represent typical weed plant community (Digitario sanguinalis-Eragrostietea minoris), annual (Sisymbrietea, Chenopodietea) and perennial ruderal vegetation (Artemisietea vulgaris, Epilobietea angustifolii), and higher successional stadia (Charabdido-Asphodeletea). Conclusions: Our survey of urban vegetation of Istanbul is the first attempt of urban vegetation classification in Turkey. We showed high diversity of vegetation due to various human impacts and Istanbul's location on the crossroads of different phytogeographical regions.
Keywords: Asia; city; phytosociology; ruderal; vegetation classification; weeds; ECOLOGICAL CHARACTERISTICS; SEGETAL VEGETATION; WASTELAND FLORA; VASCULAR FLORA; DISTRICT; FRAMEWORK; PATTERNS; SYNTAXA; TRAITS; CITY